Robot Autonomos Penyortiran dan Pemindahan Barang (Ramos) - Andre Wijaya; Dilan Rizmawan; Ari Fahrezi; Efrans Firdaus; Rizky Oriza Syahda; Wisnu Kuncoro Jati Rochman; Rahmat Hidayat (Sultan Publisher, 2025)
In the current era, as we know, the industry in the field of shipping or logistics services has experienced very rapid growth in Indonesia. Logistics is a term for storing goods on a large scale which cannot be separated from the industrial sector, including the logistics delivery services industry. The development of the expedition services market in Indonesia was stated by Mr. Feriadi, General Chair of the DPP of the Association of Indonesian Express, Postal and Logistics Delivery Service Companies 4 (Asperindo), one of which was caused by the e-commerce market which has developed rapidly. Seeing this problem, we offer a solution, namely a tool that can steer and move goods according to the destination point that has been determined based on the goods code. The product to be designed is named RAMOS (Robot Autonomous Sorter and Mover). This robot can be used in a warehouse and the robot can walk autonomously according to a predetermined destination point. Functions as a tool for sorting and moving goods in logistics warehouses. This product can reduce human effort in moving goods that have been classified, and can reduce errors in the placement of goods that have been determined. RAMOS (Autonomous Robot Sorting and Moving Goods). This robot can be used in a warehouse and the robot can walk autonomously according to a predetermined destination point. Functions as a tool for sorting and moving goods in logistics warehouses. This product can reduce human effort in moving goods that have been classified, and can reduce errors in the placement of goods that have been determined. Then, there is an advantage to this robot, namely that it is able to avoid obstacles or collisions.